85 Years' Anniversary of Alla O. Tsutsaieva (23.05.1935 – 21.03.2008) - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 301–305